La lesbienne fin-de-siècle : une fiction portugaise - Curopos, Fernando (Moderna Sprak, 2018)
La figure de la lesbienne a hanté la littérature érotique et pornographique bien avant que l'homosexualité ne soit « inventée » (Foucault) par la médecine psychiatrique dans le troisième quart du XIXe siècle. Cet article traite de la représentation de la « lesbienne » dans la littérature portugaise. littérature de siècle. Ces lesbiennes, créées par et destinées à un public masculin, sont le résultat et le produit d'un « esprit droit » (Wittig) qui fantasme les relations entre femmes tout en effaçant la réalité : la possibilité d'un véritable amour entre femmes. Néanmoins, au tournant du siècle, certaines d'entre elles sortiront du placard, plus ou moins forcées, donnant un « visage » à la lesbienne portugaise invisible
https://www.researchgate.net/publication/331274821_La_lesbienne_fin-de-siecle_une_fiction_portugaise
Keywords: approches et analyses; arts; discipline; discours dominant; europe; hétérosexisme; lesbianisme; personnes lesbiennes; portugal; ressource en ligne; régions géographiques; systèmes d'oppressions; études littéraires

Inconsequence: Lesbian representation and the logic of sexual sequence - Jagose, Annamarie (Cornell University Press, 2018)
The field of lesbian studies is often framed in terms of the relation between lesbianism and invisibility. Annamarie Jagose here takes a radical new approach, suggesting that the focus on invisibility and visibility is perhaps not the most productive way of looking at lesbian representability. Jagose argues that the theoretical preoccupation with metaphors of visibility is part of the problem it attempts to remedy. In her account, the regulatory difference between heterosexuality and homosexuality relies less on codes of visual recognition than on a cultural adherence to the force of first order, second order sexual sequence. As Jagose points out, sequence does not simply specify what comes before and what comes after; it also implies precedence: what comes first and what comes second. Jagose reads canonical novels by Charles Dickens, Henry James, Virginia Woolf, and Daphne du Maurier, drawing upon their elaboration of sexual sequence. In these innovative readings, tropes such as first and second, origin and outcome, and heterosexuality and homosexuality are shown to reinforce heterosexual precedence. Inconsequence intervenes in current debates in lesbian historiography, taking as its pivotal moment the fin-de-siècle phenomenon of the sexological codification of sexual taxonomies and concluding with a reading of a post-Kinsey pulp sexological text. Throughout, Jagose reminds us that categories of sexual registration are always back-formations, secondary, and belated, not only for those who identify as lesbian but also for all sexual subjects.
Keywords: approches et analyses; arts; discipline; discours dominant; littérature; personnes lesbiennes; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; études littéraires